1993
DOI: 10.1177/002580249303300311
|View full text |Cite
|
Sign up to set email alerts
|

Season, Climate and Suicide in Singapore

Abstract: In Singapore, an island city state in the tropics, climatic variables like sunlight, windspeed, temperature, rainfall and humidity are significantly correlated with subgroups of suicidal subjects such as Malays, young adults and youths. In the young age group (0-19 years) the relationship between meteorological factors and suicide appear to be greater than in the other two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…The results of the present study indicate that the suicide curve by month is more or less similar to that in the temperate countries, i.e. a drop during the winter months of November to February and rise in March and April, 31 the slight difference being that the peak is found in April and May in the present study, the difference is most probably due to change in months of the corresponding season at two places. Durkheim 32 believed that seasonal variation of suicidal behaviour was determined by the intensity of communal life and the activity.…”
Section: Discussionsupporting
confidence: 68%
“…The results of the present study indicate that the suicide curve by month is more or less similar to that in the temperate countries, i.e. a drop during the winter months of November to February and rise in March and April, 31 the slight difference being that the peak is found in April and May in the present study, the difference is most probably due to change in months of the corresponding season at two places. Durkheim 32 believed that seasonal variation of suicidal behaviour was determined by the intensity of communal life and the activity.…”
Section: Discussionsupporting
confidence: 68%
“…Kok [35] reported a strong relationship between climatic variables such as temperature, wind speed, rainfall and humidity and suicide in Singapore. Using regression analysis in France, Souetre et al [73] noted that among all the variables analyzed, the main factors affecting the regional distribution of suicide were ambient temperature and sunlight duration.…”
Section: Past Researchmentioning
confidence: 99%
“…Linkowski and coworkers [1992] in a study in Belgium showed that the seasonal distribution of violent suicides but not of nonviolent suicides covaried negatively with sunlight duration. In a study in Singapore, Kok and Tsoi [1993] found the total monthly number of suicides inversely correlated with average monthly hours of sunlight. Maes et al [1994] in Belgium found the annual rhythm in violent suicide synchronized with the annual rhythm in sunlight duration.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have reported seasonal variation in the occurrence of suicide, with a peak in spring and summer seasons and a trough in fall and winter months [Soue Ãtre et al, 1987;Maes et al, 1993;Chew and McCleary, 1995;Flisher et al, 1997;Ho et al, 1997;Preti, 1997Preti, , 1998Yip, 1997;Hakko et al, 1998;Rihmer et al, 1998;Altamura et al, 1999]. Meteorological factors have been hypothesized to be important in the etiology of suicide, with the amount of sunlight exposure thought to be either positively [Soue Ãtre et al, 1987;Maes et al, 1994;Preti, 1997;Salib, 1997;Salib and Gray, 1997] or inversely related to suicide [Soue Ãtre et al, 1990;Linkowski et al, 1992;Kok and Tsoi, 1993;Tietjen and Kripke, 1994;Preti, 1998]. …”
Section: Introductionmentioning
confidence: 99%